Scope of rehabilitation for patients with long COVID symptoms in Bangladesh - MD. Waliul Islam; Ehsanur Rahman; K. M. Amran Hossain; Md. Zahid Hossain (Frontiers in Rehabilitation Sciences)
BackgroundThe Bangladeshi healthcare system had planned to meet the long-term rehabilitation needs of people who had suffered due to COVID, as well as those whose health and level of activity had declined during the COVID pandemic. The goal is to apply the COVID-19 Yorkshire Rehabilitation Scale (C-YRS) to ascertain the number of health domains in which a person with PCS should undergo rehabilitation.MethodsWe carried out a quantitative cross-sectional study. The eight administrative divisions provided the pool of participants for selecting the 409 people comprised by the stratified sampling. We collected data using a semi-structured questionnaire that included sociodemographics, a symptoms checklist, and the C-YRS.ResultsThe most common post-COVID symptoms among the participants were fatigue (34.3%), muscle pain (20%), and dyspnea (12.2%). The comparison between pre- and postinfection symptoms revealed a notable increase in symptom severity and functional impairments. The study also found a significant relationship between symptom severity and place of residence (p < 0.5). The study found that the severity of symptoms was mild (30.5% (n = 90), moderate 55.3% (n = 186), and severe 14.2% (n = 94). We also looked for correlations between symptom severity, functional impairment, and health. It showed a significant positive correlation between symptom scores and functional difficulty scores (0.889, p < 0.001), while there was a significant negative correlation between symptom scores and overall health (−0.658, p < 0.001).ConclusionSeverity phenotypes can aid in the stratification of people with PCS for targeted therapies and rehabilitation care planning.